Hepcidin Gene Promoter c.-1010T and c.-582G Variants are Modulators of Iron Overload Development in Individuals Carrying the H63D Mutation in the HFE Gene - Silva, Bruno (2012)
Mutated HFE gene/protein is usually associated with Hereditary Hemochromatosis (HH). Despite C282Y being the most common HH-associated HFE mutation, others, such as H63D, also have an uncertain role in the pathogenesis of HH. Hepcidin is a crucial regulator of systemic iron homeostasis, controlling both iron absorption by enterocytes and its release by macrophages. Mutations in Hepcidin gene (HAMP) result in the development of a juvenile type of HH. Also, it has been hypothesized that, in certain conditions, some HAMP polymorphisms can modulate iron status. As example, c.-582A>G polymorphism in HAMP promoter can increase serum ferritin levels in beta-thalassemia major patients, but not in normal individuals. HAMP promoter polymorphisms were analysed by DNA sequencing in 266 individuals with ferritin levels higher than 400ng/mL: i) 191 individuals homozygous or heterozygous for the H63D mutation (group 1) and ii) 75 individuals carrying one or more C282Y alleles (HH/CY, HH/YY or HD/CY) (group 2). Also, luminescence assays were performed in Huh-7 cells in order to assess whether the HAMP promoter polymorphisms are changing the hepcidin expression in response to external stimulus. The results revealed that c.-582A>G is in linkage with c.-1010C>T polymorphism. These polymorphisms were found in a significant higher frequency in group 1 (31.2% of allele G and T, respectively) than in the general population (16.4%; p<0.001). Furthermore, they were found at a slight higher, but not significant frequency at group 2 (21.3%), comparing with general population (p=0.186). Functional in vitro studies, using stimulus as holo-transferrin, ferric citrate, IL-6, hypoxia or GDF15, revealed no differences in the activity of the HAMP promoter in the presence or absence of these polymorphisms. We conclude that c.-1010C>T and c.-582A>G polymorphisms seem to modulate iron overload development in individuals carrying the H63D mutation. However, the mechanism subjacent to this observation remains elusive.